Development Of Smart App Creator 3 (SAC) Learning Media In Learning History To Increase Students' Interest In Learning At Senior High School 3 Magelang - Saputro, Pradata Ardi; Miftahuddin, Miftahuddin (International Education Trend Issues, 2024)
This research has: 1) the purpose of developing history learning media using the Smart App Creator 3 (SAC) application; and 2) to determine the feasibility of learning media using the Smart App Creator 3 (SAC) application. This research uses the Research and Development (R&D) method using the Analyze, Design, Development, Implementation, and Evaluate (ADDIE) model. This research was conducted at SMA Negeri 3 Magelang. The small group test subjects were 34 students, while the large group test subjects were 108 students. Data analysis used qualitative data (observation and interview) and quantitative data (questionnaire). The results of product development have produced history learning media based on the Smart App Creator 3 (SAC) application. The product was assessed by material experts and media experts with a score of 94 and 103 included in the criteria of good/worthy of use and the results of the large group trial scored 86 in high criteria so that the media is suitable for use in learning History at SMA Negeri 3 Magelang.